Sleeve gastrectomy improves lipid dysmetabolism by downregulating the USP20-HSPA2 axis in diet-induced obese mice - Zhang, Wenjie; Shi, Bowen; Li, Shirui; Liu, Zenglin; Li, Songhan; Dong, Shuohui; Cheng, Yugang; Zhu, Jiankang; Zhang, Guangyong; Zhong, Mingwei (Frontiers in Endocrinology, 2022)
Obesity is a metabolic disease accompanied by abnormalities in lipid metabolism that can cause hyperlipidemia, non-alcoholic fatty liver disease, and artery atherosclerosis. Sleeve gastrectomy (SG) is a type of bariatric surgery that can effectively treat obesity and improve lipid metabolism. However, its specific underlying mechanism remains elusive. Here, we performed SG, and sham surgery on two groups of diet-induced obese mice. Compared to the sham group, the SG group displayed a downregulation of deubiquitinase ubiquitin-specific peptidase 20 (USP20). Moreover, USP20 could promote lipid accumulation in vitro. Co-immunoprecipitation and mass spectrometry analyses showed that heat-shock protein family A member 2 (HSPA2) potentially acts as a substrate of USP20. HSPA2 was also downregulated in the SG group and could promote lipid accumulation in vitro. Further research showed that USP20 targeted and stabilized HSPA2 via the ubiquitin-proteasome pathway. The downregulation of the USP20-HSPA2 axis in diet-induced obese mice following SG improved lipid dysmetabolism, indicating that USP20-HSPA2 axis was a noninvasive therapeutic target to be investigated in the future.